Códigos velados na ciência: docentes negras e seus despachos na encruzilhada do ensino superior - Tavares, Lisiane dos Santos (2025)
This dissertation examines the presence and challenges faced by Black women in Brazilian higher education teaching, understanding their trajectories as expressions of resistance, ancestral knowledge, and political struggle. The research draws from the author’s experience and from the narratives of other Black female professors, articulating memory, intersectionality, and critical epistemologies. The methodological approach combines qualitative and quantitative strategies, including interviews and content analysis, to investigate how structural and institutional racism, together with epistemicide, affect the permanence and legitimacy of these women in academia. Findings show that the presence of Black women professors, although still a minority, represents a subversive act against traditional power structures and is essential for building a more plural, democratic, and anti-racist university.